Quo vadis sustainable funds? Sustainability and taxonomy-aligned disclosure in Germany under the SFDR - Nikolai Badenhoop; Angelina Hackmann; Christian Mücke; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2023)
This paper analyzes the current implementation status of sustainability and taxonomy-aligned disclosure under the Sustainable Finance Disclosure Regulation (SFDR), which aims to improve the classification of sustainability credentials of financial products and thereby prevent greenwashing. Moreover, it considers the development of the SFDR categorization of funds offered via banks in Germany between September 2022 and March 2023. Examining data provided by WM Gruppe, which consists of more than 10,000 investment funds and 2,000 index funds, we have observed a significant proportion of Article 9 (dark green) funds transitioning to the group of Article 8 (light green) funds, particularly among index funds. As a result of this process, the profile of the SFDR classes has sharpened, which is reflected in an increased share of sustainable investments in the group of Article 9 funds. When differentiating between environmental and social investments, the share of environmental investments has increased, but the share of social investments has decreased in the group of Article 9 funds at the beginning of 2023. The share of taxonomy-aligned investments is very low, but increases slightly for Article 9 funds. However, as of March 2023, only about 1,000 funds have reported their sustainability proportions, and this picture may change due to regulatory changes that will require all funds within the scope of the SFDR to report these proportions in their annual reports being published after 1 January 2023.
Keywords: 330; SFDR; Sustainabilty; Taxonomie; Disclosure; Sustainable Investments